Contemporary Analysis of Louis Vuitton Moët Hennessy: Strategic Variables Affecting the Business Performance - Rommel Maglaya (Newinera Publisher, 2022)
This report concentrates on LVMH, the largest producer of luxury goods globally. Moreover, this paper explores the three prevailing strategic variables which collectively affect the business performance of LVMH. LVMH, a company that operates across various sectors such as fashion and leather goods, perfumes and cosmetics, watches and jewellery, and wines and spirits, is subject to various strategic influences that have implications for its operations and expansion. Furthermore, this report aims to determine an appropriate strategy to tackle the conditions faced by LVMH, relying upon the strategic management concepts, frameworks, and models presented in the class. Ultimately, this paper recommends that LVMH should implement diversified strategies to effectively address the preferences of the younger generation and their customer base. The strategy should leverage technological progress and the prevailing patterns that impact the sales and manufacturing of commodities. To enhance its success, LVMH should consider investing in more effective management practises. It should consider targeting a wide range of demographic groups. LVMH could enhance its market reach and alleviate consumer research efforts by broadening its retail distribution channels and offering luxury-priced merchandise. The implementation of the suggested strategies should be carried out in a synchronised manner while embracing a prolonged outlook.